Cataclysmic Variables with Evolved Secondaries and the Progenitors of AM CVn Stars - Podsiadlowski, P; Han, Z; Rappaport, S (2001)
We present the results of a systematic study of cataclysmic variables (CVs) and related systems, combining detailed binary-population synthesis (BPS) models with a grid of 120 binary evolution sequences calculated with a Henyey-type stellar evolution code. In these sequences, we used 3 masses for the white dwarf (0.6, 0.8, 1.0 Msun) and seven masses for the donor star in the range of 0.6-1.4 Msun. The shortest orbital periods were chosen to have initially unevolved secondaries, and the longest orbital period for each secondary mass was taken to be just longer than the bifurcation period (16 - 22 hr), beyond which systems evolve towards long orbital periods. These calculations show that systems which start with evolved secondaries near the end or just after their main-sequence phase become ultra-compact systems with periods as short as 7 min. These systems are excellent candidates for AM CVn stars. Using a standard BPS code, we show how the properties of CVs at the beginning of mass transfer depend on the efficiency for common-envelope (CE) ejection and the efficiency of magnetic braking. In our standard model, where CE ejection is efficient, some 10 per cent of all CVs have initially evolved secondaries (with a central hydrogen abundance X_c < 0.4) and ultimately become ultra-compact systems (implying a Galactic birthrate for AM CVn-like stars of 10^{-3} yr^{-1}). Almost all CVs with orbital periods longer than 5 hr are found to have initially evolved or relatively massive secondaries. We show that their distribution of effective temperatures is in good agreement with the distribution of spectral types obtained by Beuermann et al. (1998).